DGJ method for fractional initial-value problems - Li, Huan; Hu, Yue (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, a new iterative method (DGJM) is used to solve the nonlinear fractional initial-value problems(fIVPs). The fractional derivative is described in the Caputo sense. Approximate analytical solutions of the fIVPs are obtained. The results of applying this procedure to the studied cases show the high accuracy and efficiency of the approach.